(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
This survey- correlational study was conducted to find out the relationship of Decoding and Vocabulary Skills to the comprehension skills of Junior High School students. One hundred Twenty- five (125) students were the subjects of this study from Infant Jesus Academy, Kalibo in the School Year 2016- 2017. The dependent variable in this study was the Comprehension Skills while the independent variables were Decoding and Vocabulary Skills. Primary data were used in this study. It underwent validation and analysis. The descriptive statistics used were frequency, percentage, mean and standard deviation and the inferential statistics used were the Pearson r and linear regression to correlate the results of Decoding and Vocabulary skills to Comprehension Skills of students. The level of significance was set at 5%. Major findings of the study revealed that the students’ Decoding skills is “very competent” while the level of Vocabulary and Comprehension skills of students is “competent”. On the other hand, there is no significant relationship between the Decoding Skills and Comprehension Skills of the students. However, there is a significant relationship in the Vocabulary Skills and Comprehension Skills of students. The results of the students’ Vocabulary Skills are significant predictors to the Comprehension Skills of Junior High School students.